Stealing Nazi Secrets in World War II : an Interactive Espionage Adventure - Raum, Elizabeth (North Mankato, MN : Capstone Press, 2016)
"In You Choose format, follows the path of three World War II spies. The reader's choices reveal the historical details from the perspective of a wireless operator, a photo reconnaissance pilot, and a spy living in enemy territory"--
Includes bibliographical references (page 111) and index.
Keywords: World War, 1939-1945 -- Juvenile literature. -- Secret service -- United States; Espionage -- Juvenile literature. -- History -- 20th century -- United States; Spies -- Juvenile literature. -- History -- 20th century -- United States